A29 THE EVOLVING INCIDENCE OF INFLAMMATORY BOWEL DISEASE: WHAT WILL THE FUTURE HOLD?. (15th March 2019) - Coward, S; Benchimol, E I; Clement, F; Hazlewood, G; Kuenzig, E; McBrien, K; Deardon, R; Panaccione, R; Seow, C; Windsor, J W; Kaplan, G G
Abstract: Background: Incidence of Inflammatory Bowel Disease (IBD)—Crohn's Disease (CD) and ulcerative colitis (UC)—is decreasing in some provinces, but increasing in pediatrics. Even with this decrease in incidence, prevalence will continue to rise until incidence equals to mortality. Decision makers require accurate data on the current and future burden of IBD for resource planning to ensure IBD patients receive proper care. Aims: 1. Assess current and forecast future IBD incidence trends; 2. determine IBD mortality rates; and, 3. use mortality to calculate the threshold that incidence must approximate to stabilize prevalence. Methods: Using population-based data from Alberta, annual incidence (per 100, 000 persons) is calculated from 2010 to 2015, stratified by pediatric (<18), adult (18–64), and elderly (65+). Incidence is calculated for CD and UC separately, and for total IBD, which includes IBD type unclassifiable. Data is age- and sex-standardized to annual Canadian populations. Poisson regression (or negative binomial regression, when appropriate) is used to analyze historical trends and calculate average annual percentage change (AAPC) with 95% confidence intervals (CI). Log-linear models are used to forecast incidence to 2030 with 95% prediction intervals (PI). Overall standardized mortality ratios (SMR) with 95% CI are calculated for IBD, CD, and UC from 2010 to 2015—as compared to the Canadian population. The incidence threshold is calculated to determine an incidence rate that approximates mortality, which would stabilize IBD prevalence. Results: Table 1 provides age-stratified IBD, CD, and UC incidence and AAPC. Overall IBD incidence is stable from 2010 to 2015 (AAPC:−2.0, 95%CI: −4.2, 0.2). However, subtype-specific IBD incidence in adults is decreasing for CD (AAPC:−5.5; 95%CI: −7.7, −3.2) and UC (AAPC:−4.8; 95%CI: −8.6, −0.8). Figure 1 shows historical and forecasted incidence of IBD, CD, and UC. The SMR of IBD is 1.41 (95%CI: 1.34, 1.48); CD is 1.48 (95%CI: 1.38, 1.59); and, UC is 1.20 (95%CI: 1.09, 1.31). The threshold when incidence approximates mortality—so that the prevalence of IBD stabilizes—is 7.8 per 100, 000. Forecasting models show that IBD incidence in 2030 (21.6; 95%PI: 10.9, 32.4) exceeds this threshold. Conclusions: The 2030 forecasted incidence (21.6 per 100, 000 persons) exceeds the threshold required to reduce the prevalence of IBD. Future interventional research focused on prevention is urgently required to mitigate the rising burden of IBD. Funding Agencies: CIHRIzaak Walton Killam Memorial Scholarship; Eyes High Doctoral Recruitment Scholarship